Understanding Open Knowledge in China: A Chinese Approach to Openness? - Montgomery Lucy; Ren Xiang (Cultural Science)
This paper examines the development of open knowledge in China through two case studies: the development of Chinese open access (OA) journals, and national-level OA repositories. Open access and open knowledge are emerging as a site of both grass-roots activism, and top-down intervention in the practices of scholarship and scholarly publishing in China. Although the language, vision and strategies of the global open knowledge movement are undoubtedly present, so too are the messy realities of open access and open knowledge innovation in a local context. In attempting to position open access developments in China within a diverse and contested global landscape of open knowledge innovation we draw on Moore’s (2017) conception of open access as a boundary object: an object that is understood differently within individual communities but which maintains enough structure to be understood between communities (Moore 2017; Star and Griesemer 1989). Viewed as a boundary object, the concept of open knowledge is making it possible for China to engage with the global open knowledge movement, as a beneficiary of the innovation of others, and as an open knowledge innovator in its own right.